ISOLASI DAN IDENTIFIKASI JAMUR PENGHASIL MIKOTOKSIN PADA BIJI KAKAO KERING YANG DIHASILKAN DI FLORES - Emilia Simpllisiu Ake Wangge; Dewa Ngurah Suprapta; Gusti Ngurah Alit Susanta Wirya (Journal of Agricultural Science and Biotechnology, 2012)
A study entitled “Isolation and Identification of Mycotoxin-producing Fungi on Cocoa Beans Produced in Flores” was done in order to know the population and species of fungi and to know the concentration of mycotoxin in the dried cocoa beans. The dry cocoa beans used in this study were collected from several locations in Flores. Isolation of the fungi was done using Sabouraud Dextrosa Agar (SDA), while the determination of mycotoxin concentration was done based on Enzym Linked Immunosorbent Assay (ELISA). Results of this study showed that,  there were several fungi were found in the dried cocoa beans produced in Flores, namely Aspergillus niger, A. flavus, A. parasiticus, A. fumigatusandMucor sp. All tested dried cocoa beans contained aflatoxin B1, where the highest aflatoxin B1 concentration was found in the fermented beans from West Manggarai with the concentration at 3.65 ppb, while the lowest concentration was 2.21ppb, which was found in the cocoa beans from Nagekeo. The highest concentration of ochratoxin A was 0.38  ppb, which was found in the cocoa beans from West Manggarai, while no ochratoxin A was detected in the cocoa beans from Ende.